EVALUASI SISTEM PENGENDALIAN INTERN ATAS PENGELOLAAN ASET TETAP PADA PEMERINTAH KABUPATEN BREBES - Alvianita Gunawan Putri (Faculty of Economic and Business Universitas STIKUBANK, 2017)
The purpose of this study is to evaluate the internal control system for the management of fixed assets and assess the obstacles faced in managing fixed assets in the Government of Brebes Regency. This type of research is a case study with a qualitative approach using descriptive methods. Effectiveness is assessed using 5 (five) elements of the Internal Control System by giving weight to each element. Assessment is done by assessing the results of interviews using the Internal Control Questionnaire (ICQ) test list that refers to PP No. 60 of 2008 and equipped with observations and documents. Based on the results of the interview completed with the results of observations and documents, the results obtained were the elements of the control environment were given a weight of 30% so as to obtain a value of 27.27%. Risk assessment is given a weighting of 20% so as to obtain a value of 8.57%. Control activities are given a weighting of 25% so as to obtain a value of 19.70%. Information and communication are given a weight of 10% so that they get a value of 7.88%. Monitoring was given a weighting of 15% so that it obtained a score of 10.18%. The total value of 5 (five) elements of the internal control system in the Government of Brebes Regency is 73.60% which are classified as effective criteria. Keywords: management of fixed assets, internal control systems (spi).